O curso de graduação em psicologia da Pontifícia Universidade Católica de Goiás na trajetória da institucionalização do ensino superior da psicologia no Estado de Goiás - Rodrigues, Divino de Jesus da Silva (2010)
This research deals with the institutionalization of psychology courses in higher education in the State of Goiás, in 1973 at the Pontifical Catholic University of Goias. Part of the history of psychology in Brazil since the formation of "ideas" to the psychological constitution of scientific psychology, and tries to recover the elements of this story in Goiás. State To do so, demonstrates the organization of undergraduate education in psychology in Brazil through data-and MEC, Register of Higher Education, Ministry of Education - MEC, the National Institute of Educational Studies and Research Teixeira - INEP, the Brazilian Association of Education in Psychology - ABEP, the National Association of Search and Post Graduate Psychology - ANPEPP, the Brazilian Association of Higher Education Maintainers - ABMES, consultancy firms and educational institutions that teach the Psychology Course in the country. Finally, comes the creation of the Psychology Course in Higher Education of the State of Goiás, producing a historical view on the creation of the Pontifical Catholic University of Goias, the Office of Orientation to the Graduate, research and systematization of their history.